Pengaruh Edukasi Covid-19 Terhadap Tingkat Kecemasan Ibu Hamil: Literatur Review - Darma Andini; Dwi Yati (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: Pregnant women are a vulnerable group for contracting COVID-19. This vulnerability makes pregnant women experience anxiety. Education is needed to provide information related to COVID-19 and is expected to change the level of anxiety. This study explains how the literature regarding changes in the level of anxiety of pregnant women during the COVID-19 pandemic. Objectives: To see the effect of COVID-19 education on the anxiety level of pregnant women. Methods: A systematic review of the literature with a minimum range of 2019, using several databases (Google Scolar, Science Direct, Semantic Scholar and Pubmed). Results: The COVID-19 education process for pregnant women began by giving a questionnaire to see the anxiety of pregnant women, then a COVID-19 educational intervention was carried out using counseling, lectures and tele-education methods on the topic of COVID-19, preparation for pregnancy and childbirth during the COVID-19 pandemic. using the powerpoint method, leaflets and booklets. Then do a posttest intervention to see changes in anxiety levels. After education, it was found that the level of anxiety decreased in all reviewed journals with each decreasing rate of 12.4%, 3.9%, 3.12%, and 5.04%. Conclusion: COVID-19 education carried out on pregnant women can change the level of anxiety to decrease.